2017
DOI: 10.4244/eij-d-16-00909
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation is a predictor of mortality after percutaneous mitral valve edge-to-edge repair

Abstract: More than half of patients undergoing PMVR have concomitant moderate/severe TR, which is associated with a worse outcome. Among predictors of mortality after edge-to-edge PMVR, severe TR at baseline is the most important. Patients with no improvement of TR at 30 days after PMVR have a significantly higher mortality at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…Importantly, recent studies have demonstrated an already increased in‐hospital and early mortality in patients who were treated for severe MR by the edge‐to‐edge repair technique and suffered from concomitant severe or even moderate TR . According to the available literature, one cannot infer a spontaneous improvement of severe TR after edge‐to‐edge mitral valve repair: a reduction of TR can be seen in less than 50% of patients with moderate to severe TR, actually the percentage of severe TR in this report by Yzeiraj et al . did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent studies have demonstrated an already increased in‐hospital and early mortality in patients who were treated for severe MR by the edge‐to‐edge repair technique and suffered from concomitant severe or even moderate TR . According to the available literature, one cannot infer a spontaneous improvement of severe TR after edge‐to‐edge mitral valve repair: a reduction of TR can be seen in less than 50% of patients with moderate to severe TR, actually the percentage of severe TR in this report by Yzeiraj et al . did not change.…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of the patients undergoing percutaneous edge‐to‐edge repair of the mitral valve, and more than 25% of the patients undergoing transcatheter AVR have at least moderate TR. Residual TR after transcatheter mitral and aortic valve procedures is an independent predictor of mortality 23,24 …”
Section: Commentmentioning
confidence: 99%
“…Low LAI indicates a leaflet-to-annulus disproportionality and significantly predicts residual MR after TMVr [32] . Identifying patients with inadequate MR reduction is important as relevant residual MR is associated with worse survival rates in several studies [33][34][35][36][37] .…”
Section: Pmr Only Collectivementioning
confidence: 99%